Personal Satisfaction with Accessibility and Service Quality: Spatial Justice in Guangzhou’s Social Housing Communities - Ruixia Chao; Haolin Hong; Wei Wei (Urban Science)
Individuals in social housing heavily depend on the surrounding infrastructure and services. There is a gap in understanding the needs of vulnerable groups regarding access to these resources. From the lens of spatial justice, we explored the specific needs of financially limited residents, considering affordability, service levels, and service quality. Surveying 660 individuals across 13 communities in Guangzhou, we firstly assessed the accessibility to facilities by using travel data. Subsequently, a principal component analysis revealed key factors influencing individuals’ satisfaction, including proximity to essential amenities, efficient service, high-quality education, affordability of commercial establishments, and access to healthcare services. While proximity to basic facilities achieves satisfaction, it falls short of ensuring fulfilment in healthcare, commerce, and education service quality. Satisfaction varies by community location and age, with newer communities, especially those established post-2010 in outlying areas, struggling to uphold spatial justice.